1983
DOI: 10.1002/cne.902210405
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the efferent projections of the medial superior olivary nucleus in the cat as revealed by HRP and autoradiographic tracing methods

Abstract: Features of the organization of the efferent axonal projections from the medial superior olivary nucleus (MSO) in the cat were studied. In order to determine the origin and distribution of projections from MSO, the retrograde horseradish peroxidase (HRP) and autoradiographic tracing methods were used. The results showed that (1) in both HRP and autoradiographic studies the projection to the inferior colliculus was largely ipsilateral, although a contralateral component was present; (2) the projection field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 31 publications
6
58
1
Order By: Relevance
“…Interestingly, three of four neurons had highly oriented dendrites, one in the central nucleus and two in the dorsal cortex. Their presence in the dorsal cortex is consistent with findings that show MSO fibers penetrating into the low-frequency part of the dorsal cortex (Henkel and Spangler, 1983;Oliver and Beckius, 1993). Thus, both subdivisions may inherit their I TD sensitivity from a common input.…”
Section: Interaural Time Differences: Heterogeneity Of Responsessupporting
confidence: 89%
“…Interestingly, three of four neurons had highly oriented dendrites, one in the central nucleus and two in the dorsal cortex. Their presence in the dorsal cortex is consistent with findings that show MSO fibers penetrating into the low-frequency part of the dorsal cortex (Henkel and Spangler, 1983;Oliver and Beckius, 1993). Thus, both subdivisions may inherit their I TD sensitivity from a common input.…”
Section: Interaural Time Differences: Heterogeneity Of Responsessupporting
confidence: 89%
“…All neurons of the mammalian ventral cochlear nucleus, some of which phase-lock to acoustic stimuli (Lavine, 197 1;Goldberg and Brownell, 1973;Rose et al, 1974), have been reported to contain CaBP (Jande et al, 198 1;Garcia-Segura et al, 1984) in the rat. The medial superior olive, which also contains phase-locking neurons (Moushegian et al, 1967;Goldberg and Brown, 1969) and is thought to be the mammalian homolog of the avian NL (Ramon y Cajal, 1908), projects to a region in the ventrolateral portion of the ICC (Van Noort, 1969;Elverland, 1978;Henkel and Spangler, 1983). CaBP-immunoreactive fibers, which have been reported in the mammalian inferior colliculus (Garcia-Segura et al, 1984), may be restricted to the ventrolateral sector.…”
Section: Discussionmentioning
confidence: 99%
“…If so, we would expect a tendency for neighboring neurons to have the same type of frequency response map because there is considerable anatomical evidence that projections from different brain stem nuclei are at least partially segregated in ICC (Henkel and Spangler 1983;Oliver et al 1997;Shneiderman and Henkel 1987). Contrary to this prediction, analysis of the distribution of response maps among neighboring unit pairs revealed no significant deviation from a random distribution across recording sites, suggesting a complex organization and mixing of these different functional response patterns within local regions.…”
Section: Width Of Frequency Tuning and Response Area Typesmentioning
confidence: 95%
“…Incoming axons run parallel to these sheets. The input from lower nuclei tend to form distinct projection bands that partly interleave and partly overlap with axon bands from other nuclei (Henkel and Spangler 1983;Oliver et al 1997;Shneiderman and Henkel 1987).…”
Section: Introductionmentioning
confidence: 99%